Simultaneous Determination of Pesticide Residues and Mycotoxins in Storage Pu-erh Tea Using Ultra-High-Performance Liquid Chromatography Coupled with Tandem Mass Spectrometry - Siu Leung Chau; Aihua Zhao; Wei Jia; Lu Wang (Molecules, 2023)
Mycotoxins and pesticides are the most concerning chemical contaminants that can affect the quality of Pu-erh tea during its production and storage. This study presents a method that can simultaneously determine 31 pesticide residues and six mycotoxins in Pu-erh tea within 11 min using ultra-high-performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS) after QuEChERS extraction. The lower limit of quantification (LOQ) for all analytes ranged between 0.06 and 50 ppb. Recoveries for each pesticide and mycotoxin ranged between 62.0 and 130.3%, with intra- and inter-day precisions lower than 15%. Good linear relationships were obtained, with correlation coefficients of r2 > 0.991 for all analytes. The established method was applied to 31 Pu-erh tea samples, including raw and ripened Pu-erh tea with different storage times. As a result, pesticide residues were not detected in any of the collected samples, and the mycotoxins detected in the samples were well below the official maximum residue limits (MRLs). Notably, the levels of aflatoxin B1 (AFB1), aflatoxin G1 (AFG1) and aflatoxin G2 (AFG2) were lower than 1 ppb in the samples stored for more than 30 years.